Fatwa Sesat Syiah dan Legitimasi Kekerasan (Menguji Buku Mengenal dan Mewaspadai Penyimpangan Syi’ah di Indonesia dengan Teori Toulmin) - Wildan Imaduddin Muhammad (Nizham Jurnal Studi Keislaman, 2017)
Recently, Shi’a-Sunni’s controversy in Indonesia increase dramatically as occurring as geo-political clash in the Middle East, particularly between Saudi Arabia and Iran. The culmination of Indonesian Shi’a’s conflict is assigned by expulsion several communities from their home and village. Afterward, that’s discrimination is legitimated by the book of MUI entitled Mengenal dan Mewaspadai Penyimpangan Syi’ah di Indonesia. This article aims to review the book’s contents by using linguistic philosophy in form of Stephen Toulmin’s theory of argumentation. Stephen Toulmin is professor of Linguistic Philosophy Studies at Cambridge University. He develops six concepts for examine argumentation namely data, claim, warrants, backing, qualifier and rebuttal. Dialectically, its six concepts is related each other to form an argumentation. A good argumentation, as Toulmin’s opinion, is arranged from factual and objective data, supported by strong warrants and backing, truthful qualifier, and can defend from rebuttal. As one of result, this research shows that the correlation between data and claim in MUI’s book categorized as unilateral fact that produces negative issues and impacts to discriminative action for Shi’a community.